Photon Scalar/Pseudoscalar Mixing Dynamics in Magnetized Media - Manoj K. Jaiswal; Avijit K. Ganguly (Research Trends and Challenges in Physical Science Vol. 3, 2021)
We study the dynamics of photon-scalar interaction (mixing) by operators of mass dimension five (predicted in numerous theories, beyond standard model), in various kinds of media. Our main objectives are to study medium specific modifications to the mixing dynamics of of photons with pseudoscalar (axion a(x)) and scalar e.g., dilaton, moduli etc. (denoted by ) dark matter candidates. We look into spectro-polarimetric as well as oscillation aspects of the same and their possible astrophysical consequences.